Walking the tightrope of real exchange rate policy for development: The roles of targets, instruments, and saving rates - Arslan Razmi (University of Massachusetts, Department of Economics, 2019)
Real exchange rate policy can potentially be utilized to target the trade balance and/or development through capital accumulation. However, the presence of distributional conflict and the trade-off between current and future trade imbalances complicates matters. I show that policy assignment matters for dynamic stability. Moreover, the relative saving behavior of different functional income groups influences dynamic behavior. The analysis sheds light on why real exchange rate policy may often be unfeasible, even if desirable from a developmental perspective.
Keywords: F43; F63; O16; E63; 330; Policy assignment; real exchange rates; investment subsidies; external balance